2005
DOI: 10.1002/uog.1860
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study of first‐trimester screening for trisomy 21 in 75 821 pregnancies: results and estimation of the potential impact of individual risk‐orientated two‐stage first‐trimester screening

Abstract: Objectives To evaluate the performance of first-trimester screening for trisomy 21 by a combination of maternal age, fetal nuchal translucency (NT) and maternal serum free β-human chorionic gonadotropin (β-hCG) and pregnancy-associated plasma protein-A (PAPP-A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
296
1
31

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(338 citation statements)
references
References 25 publications
8
296
1
31
Order By: Relevance
“…towards the placenta from the fetal heart, instead of towards the heart from the placenta) in 64% of Down's syndrome pregnancies and 4% of pregnancies with a normal outcome. 1 Several studies show that DV blood flow is a useful discriminatory test either in selected higher-risk populations 2,3 or in other populations. 4,5 DV blood flow can also be expressed quantitatively as the ductus venosus pulsality index (DVPI), which is the difference between the maximum blood velocity in systole and that at the end of diastole (A-wave) in the DV divided by the maximum velocity averaged over the time of one heartbeat, as follows: DVPI ¼ Systole velocity À End diastole velocity Average maximum velocity during one heart beat :…”
Section: Introductionmentioning
confidence: 99%
“…towards the placenta from the fetal heart, instead of towards the heart from the placenta) in 64% of Down's syndrome pregnancies and 4% of pregnancies with a normal outcome. 1 Several studies show that DV blood flow is a useful discriminatory test either in selected higher-risk populations 2,3 or in other populations. 4,5 DV blood flow can also be expressed quantitatively as the ductus venosus pulsality index (DVPI), which is the difference between the maximum blood velocity in systole and that at the end of diastole (A-wave) in the DV divided by the maximum velocity averaged over the time of one heartbeat, as follows: DVPI ¼ Systole velocity À End diastole velocity Average maximum velocity during one heart beat :…”
Section: Introductionmentioning
confidence: 99%
“…Все большее распространение в практике работы медико-генетических учреждений в мире находит обследование беременных с помощью ПС в I триме-стре. Выявление патологии во II триместре беремен-ности сопряжено с моральными проблемами и ря-дом акушерских осложнений, связанных с прерыва-нием беременности в поздние сроки [7,8,10,[13][14][15][16] Анализ архивного материала женской консуль-тации показал, что как раз массовый характер скри-нинга беременных в I триместре женская консуль-тация не обеспечивает. Из общего количества жен-щин, состоявших на учете по беременности с 2007 по 2011 г., в I триместре встали на учет 69,3%, а ПС проведено 59,3% беременных женщин.…”
Section: Discussionunclassified
“…Several prospective interventional studies in many thousands of pregnancies have demonstrated that for a 5% false-positive rate, the first-trimester combined test identifies about 90% of trisomy 21 pregnancies (Krantz et al, 2000;Bindra et al, 2002;Schuchter et al, 2002;Spencer et al, 2003c;Wapner et al, 2003;Nicolaides et al, 2005;Ekelund et al, 2008;Kagan et al, 2009a;Leung et al, 2009). …”
Section: Screening By Fetal Nt Thickness and Serum Biochemistrymentioning
confidence: 99%